ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR SISTEM BLENDED LEARNING PADA MATERI PROGRAM LINIER - Wiji Sugiarti; Isnurani Isnurani (LPPM Universitas Bina Bangsa, 2023)
In the midst of the Covid-19 pandemic, the government established a blended learning model as a learning solution. May encounter difficulties in its application, requiring identification of these difficulties to study effectively. The purpose of this study was to find out the internal and external variables that affect students which are the most significant causes of learning difficulties in blended learning material in linear program material in the mathematics study program at Pamulang University. Factor analysis the confirmatory factor analysis model was used in this study. The research sample consisted of 180 students of the Mathematics Study Program at Pamulang University who took linear program courses. Questionnaires and documents are used to collect data. The results of the study are: 1) there are five internal factors that cause learning problems in a blended learning system in linear program material, with learning ability being one of the five biggest contributing factors which has an Eigenvalue of 5.402 and a variance value of 33 ,7%. 2) associates, having an Eigenvalue of 5.336 and a variance value of 38.3%, is one of the four external variables that create learning problems in a blended learning system in linear programming material. Based on the findings of this study, it can be concluded that the internal factor, namely the learning ability factor, is the most significant source of learning difficulties faced by students in the blended learning system and the external factor is the social friend factor